Pemanfaatan Web Site oleh Kelompok Kreatifitas Mahasiswa Periklanan (Studi Kasus tentang penggunaan Web Site sebagai sumber inspirasi untuk membuat Iklan oleh Kelompok DE-ADLINE UGM, BOHLAM UAJY, KOMAKOM UMY, KOSTRAD UIN, KOMPOR.KOM UII, AVIKOM UPN selama Tahun 2011) - , HARDOYO, Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The needs of information for communication students for this time absolutely are needed. The uses of Internet as new media are needed much for students, especially for the creativity group of advertising students. The amount of information sources on Internet really make easier for us in choosing any site needed suitably. This media is capable of giving much information needed in processes of making any advertisement works, easy in access of the uses, have give and take relationship in getting information. Uses of Web Site by student groups of advertising creativity such as DE- ADLINE UGM, BOHLAM UAJY, KOMAKOM UMY, KOSTRAD UIN, KOMPOR.KOM UII, AVIKOM UPN. For them, Web Site is considered as inspiration sources in making advertisement. This media is capable of responding and giving reactions thus it can give impacts on behavioral changes for the users. Behavioral changes meant are activities done by advertising student groups in making advertisement in groups. Processes in making the advertisement in these organization groups can be seen based on how to use Web Site in time, tools and information accesses beside also they want to know how far activities are going on in making the advertisement, from ideas to the results of advertising production.